2020
DOI: 10.1534/genetics.119.302698
|View full text |Cite
|
Sign up to set email alerts
|

Independent Origin of XY and ZW Sex Determination Mechanisms in Mosquitofish Sister Species

Abstract: Fish are known for the outstanding variety of their sex determination mechanisms and sex chromosome systems. The western (Gambusia affinis) and eastern mosquitofish (G. holbrooki) are sister species for which different sex determination mechanisms have been described: ZZ/ZW for G. affinis and XX/XY for G. holbrooki. Here, we carried out restriction-site associated DNA (RAD-) and pool sequencing (Pool-seq) to characterize the sex chromosomes of both species. We found that the ZW chromosomes of G. affinis female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 104 publications
1
40
0
Order By: Relevance
“…Genetic-controlled sex determination systems in fish are variable, ranging from XX/XY to ZZ/ZW [ 68 ]. Fish generally do not have highly morphologically differentiated sex chromosomes, making it difficult to distinguish between autosomes and sex chromosomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic-controlled sex determination systems in fish are variable, ranging from XX/XY to ZZ/ZW [ 68 ]. Fish generally do not have highly morphologically differentiated sex chromosomes, making it difficult to distinguish between autosomes and sex chromosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Gambusia holbrooki and G. affinis are so closely related that for a long time, biologists thought they were the same species. Phylogenetic analyses estimated that their divergence time was ∼2–7 Mya [ 69 , 73 , 74 ], and other researchers showed that the XY and ZW sex determination mechanisms had independent origins in G. holbrooki and G. affinis , respectively [ 68 ]. Therefore, we speculate that the differentiation of Z and W sex chromosomes is a very recent event.…”
Section: Resultsmentioning
confidence: 99%
“…Recent findings indicated that these transitions among heterogametic systems can be favored by haploid selection ( Scott et al, 2018 ). Shifts between different sex chromosome systems (XY ↔ ZW) are also well documented across several clades of animal species and appear to be a common phenomenon, especially in reptiles, frogs, and fishes ( Vicoso et al, 2013 ; Bachtrog et al, 2014 ; Zhou et al, 2014 ; Jeffries et al, 2018 ; Pennell et al, 2018 ; Kottler et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…While micromelanophores differentiate in waves during embryonic stages to create the base pigmentation pattern, macromelanophores begin differentiation simultaneously and do so later in the fish's life to create spotting patterns (Humm and Young, 1956;Vielkind et al, 1976. Macromelanophores are 150-300 µm in diameter, approximately three times the size of micromelanophores measured in G. holbrooki (Regan, 1961;Kottler et al, 2020). Unlike micromelanophores, macromelanophores do not appear to have distance-dependent regulation, so they can overlap each other to form larger spots or blotches Anders et al, 1984).…”
Section: Pigment Cellsmentioning
confidence: 99%
“…Unlike micromelanophores, macromelanophores do not appear to have distance-dependent regulation, so they can overlap each other to form larger spots or blotches Anders et al, 1984). Both melanophore types have dendritic or stellate shapes, but macromelanophores have Myers, 1925;Regan, 1961;Angus, 1989;Horth, 2006;Kottler et al, 2020 Limia Haskins et al, 1960;Schultz and Kallman, 1968;Turner et al, 1980;Schartl et al, 1997;Lampert et al, 2007;Nanda et al, 2007;Lamatsch et al, 2010 Atz, 1962;Zander, 1965Zander, , 1967Kallman, 1971;Rauchenberger et al, 1990 Carbomaculatus, spotted Atz, 1962;Kallman and Atz, 1966;Kallman, 1975;Franck et al, 1998;Weis and Schartl, 1998;Walter et al, 2006 X. maculatus Pulchra, spotted X. maculatus (Up-2) with spotted pattern-4 2…”
Section: Pigment Cellsmentioning
confidence: 99%